2010
DOI: 10.1083/jcb.201006006
|View full text |Cite
|
Sign up to set email alerts
|

An invasive podosome-like structure promotes fusion pore formation during myoblast fusion

Abstract: An F-actin–enriched protrusion resembling an invasive podosome promotes fusion pore formation between muscle founder cells and fusion-competent myoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
408
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(432 citation statements)
references
References 67 publications
23
408
1
Order By: Relevance
“…A variety of fusion-related roles for Drosophila WASp have been proposed, including involvement in establishment of an adhesive structure between myoblasts (30), expansion of nascent fusion pores (21,26), and contribution to the formation of fusion-associated F-actin "foci" (27,32). At present, our analysis does not allow for assignment of such specific cellular roles to N-WASp as a mediator of mammalian myoblast fusion.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A variety of fusion-related roles for Drosophila WASp have been proposed, including involvement in establishment of an adhesive structure between myoblasts (30), expansion of nascent fusion pores (21,26), and contribution to the formation of fusion-associated F-actin "foci" (27,32). At present, our analysis does not allow for assignment of such specific cellular roles to N-WASp as a mediator of mammalian myoblast fusion.…”
Section: Discussioncontrasting
confidence: 41%
“…Noteworthy in this context is the observed requirement for Nap1, a regulator of the WAVE NPF, during fusion of cultured murine myogenic cell lines (25). An essential involvement of WASp/WAVE-family elements in myoblast fusion has been previously established for the different phases of Drosophila myogenesis (21,(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that, in founder cells, F-actin forms a thin sheath underlying points of cell contact (Sens et al, 2010). By contrast, within the limits of confocal microscopy, the dense actin focus appears to reside exclusively in the FCMs (Sens et al, 2010;Haralalka et al, 2011), as depicted in Figs 4, 5 and 7. These F-actin foci are formed by the action of the NPFs Scar and WASp on the Arp2/3 complex as outlined below.…”
Section: F-actin Foci F-actin Nucleating Complexes and Fusion Poresmentioning
confidence: 98%
“…Dynamic F-actin foci are formed and dissolve coincident with myoblast fusion in live embryos (Richardson et al, 2007), and actin foci are found at points of cell-cell contact in fixed tissue samples (Kesper et al, 2007;Richardson et al, 2007;Kim et al, 2007). Recent studies have shown that, in founder cells, F-actin forms a thin sheath underlying points of cell contact (Sens et al, 2010). By contrast, within the limits of confocal microscopy, the dense actin focus appears to reside exclusively in the FCMs (Sens et al, 2010;Haralalka et al, 2011), as depicted in Figs 4, 5 and 7.…”
Section: F-actin Foci F-actin Nucleating Complexes and Fusion Poresmentioning
confidence: 99%
“…The signaling intermediates include scaffold proteins (ELMO, Blown Fuse, Antisocial) (8)(9)(10), kinase (p21-activated kinase) (11), guanine nucleotide exchange factors (GEFs) [Myoblast City (MBC), Loner] (12, 13), GTPase (Rac), (14) and actin nucleation regulators (Kette, WAVE, WASP, WASP-interacting protein) (15)(16)(17)(18)(19). Some of these proteins ultimately promote the formation of actin-driven podosome-like structures in the fusion-competent cells that invade founder cells for membrane fusion (20,21).…”
mentioning
confidence: 99%